Morocco’s Comprehensive Reform in Financial Governance and Regulatory Compliance - EL YETTEFTI , Mohammed; TAOUAB , Omar (Revue Internationale du Chercheur, 2024)
Morocco’s path towards enhancing financial governance and regulatory compliance represents a significant step towards aligning with global financial standards, a movement underscored by strategic alignment, institutional restructuring, legislative reforms, international cooperation, and public-private partnerships. The country’s proactive stance, particularly in response to the FATF’s grey list, highlights its commitment to combating financial crimes, bolstering transparency, and fostering a robust financial ecosystem. The restructuring and empowerment of the ANRF, along with comprehensive legislative enhancements, showcase Morocco’s dedication to establishing a resilient, transparent, and internationally compliant financial sector. This multifaceted approach positions Morocco as an exemplar for emerging economies navigating the complexities of today’s financial landscape. The objective of this article is to provide an analytical overview of Morocco’s efforts to enhance its financial governance framework in response to global standards, focusing on reforms, strategic banking sector alignment, and the critical role of the ANRF in these processes. It examines Morocco’s response to international scrutiny, especially its proactive measures following inclusion in the FATF’s grey list and explores the integration of the private sector into financial reforms. The article proposes recommendations based on the C.R.I.M.E Internal Control Framework to further strengthen Moroccan banks and the ANRF’s internal controls and risk management practices. This comprehensive analysis aims to shed light on the challenges and opportunities facing emerging economies in the modern financial landscape.